The prevalence of depressive and anxious frameworks in the LGBTQIA+ population: a comparative study (Research, Society and Development, 2022)
Depression and anxiety are two psychiatric conditions that can affect the life quality of patients in different ways, impairing from performance in daily activities to the quality of interpersonal relationships. It is known that there are three main factors involved in the development of these conditions, which are the psychosocial, neurobiological and genetic determinants. In this regard, the present project was carried out with the objective of analyzing whether, specifically regarding the psychosocial component, members of the LGBTQIA+ community are exposed to experiences that may increase the prevalence of depressive and/or anxious conditions compared to cis- heterosexuals. The research has an observational and transversal character, constituting an inquiry study. For a better understanding of this issue, questionnaires were applied to 88 individuals, 55 of whom were cis-heterosexuals and 33 LGBTQIA+, using the Beck Anxiety Inventory (BAI) and the Beck Depression Inventory (BDI) as a basis, in addition to questions prepared by the authors. The work showed that LGBTQIA+ are subject to particular forms of discrimination and consequent psychological suffering, in addition to having a higher prevalence of possible cases of both diseases. After this, it was noticed that, despite the advances made by this minority, the intolerant view of society towards these people still contributes to a harmful reality to their mental health.